MORPHOLOGICAL AND PHONOLOGICAL VARYING SYSTEM OF GORONTALO LANGUAGE AND THE PROBLEM OF ORGANIZING THEM IN CUSTOM TERMS DICTIONARY - Kartin Lihawa; Rasuna Thalib; Agus Lahinta; Adimawati Helingo (Fakultas Sastra Universitas Negeri Malang, 2018)
Abstract: The objective of this research is to describe the morphological and phonological varying system of Gorontalo language, and its problem in organizing them in custom terms dictionary. The method used is qualitative with the data collection techniques involved observing, recording the language in a practical poem of the traditional ceremony, and other published books. The agreement of word-writing problems through workshop alignment and standardization are (1) deletion of sound y and w in certain words, (2) there is no unique phonetic symbols of apostrophe for glottal sound between two sequence vowels written side by side in a row, (3) selection of writing nt for the sound /ð/, (4) selection of particles mayi, mota, mola, mao, ma, ngo, o (for verb not for noun), hi, lo, de, dipo, ta, (5) selection of prefix po attached to the verbs, (6) variations of long and short vowels writing on certain phonemes. permalink/DOI: dx.doi.org/10.17977/um015v46i12018p008